Treatment of Severe Autoimmune Diseases with Autologous Hematopoietic Stem Cell Transplantation - Stojanoski, Zlate; Karadzova-Stojanoska, Anzelika; Pivkova Veljanovska, Aleksandra; Genadieva-Stavrik, Sonja; Cadievski, Lazar; Ivanovski, Martin; Karanfilski, Oliver; Cevreska, Lidija; Georgievski, Borche (Македонско лекарско друштво = Macedonian medical association, 2017)
Abstract Introduction. Autoimmune diseases are a family of more than 100 heterogeneous conditions that affect 5 to 8% of the world’s population. The etiology is still un-known but the disregulation of the regulatory T-lymphocytes play a central role inthe autoimmunity and the success of the long-term remission. Although conventional immunosuppression and new biological agents can provide disease control in severely affected patients, such treatments are rarely curative and alternative strategies are needed. Indeed, severe forms of systemic autoimmune diseases, such as multiple sclerosis (MS), systemic sclerosis (SSc), rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), juvenile idiopathic arthritis (JIA), hematologic immune cytopenia (HIC) and Crohn’s disease are difficult to be treated. High-dose immunosuppressive therapy followed by autologous stem cells transplantation is reliable option for a successive treatment of this group of patients. Aim. To determine the safety of the procedure of autologous stem cell transplantation in patients with autoimmune diseases and concomitant malignant hematological disorders. Methods. During a period of 15 years (from September 2000 to September 2015) at the University Clinic of Hematology in Skopje we have treated 6 patients with autoimmune disease and concomitant hematological neoplasm. None of the patients was treated for primary autoimmune diseases. Two men and 4 women, with median age of 47 years were treated. Sjogren syndrome and multiple myeloma were found in 2 patients, polyartheritis nodosa and multiple myeloma in 1 patient, rheumatoid arthritis and acute myeloblastic leukemia in 1, systemic lupus erythematosus and non-Hodgkin lymphoma in 1; severe psoriasis and acute myeloblastic leukemia in 1 patient. Results. All treated patients are alive after trans-planted procedure, with transplant related mortality day +100: 0. Conclusion. Autologous stem cell transplantation is safe and recommended option for treatment ofpatients with autoimmune disease and hematologic neoplasm.
Третман на автоимуни заболувања со автологна трансплантација на матични хематопоетски клетки